Implementasi Program Edukasi Stop Bullying pada Siswa MIS Ar-Rahman Desa Bahtangan - Suglia, Namira Fariza Isna; Neliwati, Neliwati; Hsb, Mhd Fikry Hasrul; Mukminin, Riqotul Qolbi; Harahap, Khairunnisa Aulia (Al-DYAS, 2025)
Bullying is a serious problem in education because it has negative effects on students’ psychological, social, and academic development, including at the primary education level such as MIS Ar-Rahman Desa Bahtangan, thereby underscoring the importance of appropriate prevention strategies. This study aims to describe the implementation of the Stop Bullying Education Program (Program Edukasi Stop Bullying) at MIS Ar-Rahman Desa Bahtangan and to analyze its effectiveness in enhancing students’ understanding and anti-bullying attitudes. The program was implemented through educational sessions, interactive discussions, and role-play simulations designed to cultivate understanding of the forms and impacts of bullying, strengthen empathetic attitudes, and develop students’ social skills. The findings indicate increased student knowledge regarding the forms and consequences of bullying, shifts in attitudes toward greater empathy, and higher levels of teacher engagement in building a safe school environment. The challenges encountered include limited time for implementation, the absence of written regulations, and insufficient parental support. Overall, the Stop Bullying Education Program proved effective in fostering anti-bullying awareness and has important implications for the sustainability of efforts to create a positive and child-friendly school climate.